2004
DOI: 10.1097/00005537-200409000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Voice Changes after Androgen Therapy for Hypogonadotrophic Hypogonadism

Abstract: MF0 in IHH patients is intermediate between normal male and female levels. After treatment with testosterone, these values approach the range of normal males. This prospective study details the impact of androgens on the larynx and vocal function in patients with IHH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…So far, evidence from androgen treatment of individuals lacking the masculinisation of the larynx (e.g. female-to-male transsexuals and adult males with hypogonadism) has shown that vocal folds are still sensitive to testosterone in adulthood, with testosterone injections permanently thickening the folds and thus lowering voice F0 (Akcam et al, 2004;Baker, 1999;Talaat et al, 1987;Van Borsel et al, 2000). However, the potential effects of testosterone exposure in adult males without androgen deficiencies on the physiology (vocal fold mass and length, vocal tract length and extensibility) and on the behavioural control of the vocal apparatus (Pisanski et al, 2012) remain largely unknown.…”
Section: Physiological Characteristics and Voice Cuesmentioning
confidence: 99%
“…So far, evidence from androgen treatment of individuals lacking the masculinisation of the larynx (e.g. female-to-male transsexuals and adult males with hypogonadism) has shown that vocal folds are still sensitive to testosterone in adulthood, with testosterone injections permanently thickening the folds and thus lowering voice F0 (Akcam et al, 2004;Baker, 1999;Talaat et al, 1987;Van Borsel et al, 2000). However, the potential effects of testosterone exposure in adult males without androgen deficiencies on the physiology (vocal fold mass and length, vocal tract length and extensibility) and on the behavioural control of the vocal apparatus (Pisanski et al, 2012) remain largely unknown.…”
Section: Physiological Characteristics and Voice Cuesmentioning
confidence: 99%
“…1 Former studies concerning the influence of sex hormones on the male voice mainly described changes of the voice at puberty, or dealt with effects of hormone replacement at states of pathologically low androgens levels in young populations. 7,13 These studies demonstrated very clearly effects of sex hormones on development and characterization of the male voice. No study so far investigated effects of ''physiologically'' decreased levels of sex hormones during the aging process.…”
Section: Discussionmentioning
confidence: 87%
“…2 Replacement of testosterone has been shown to diminish these effects and approaches these voices to those of normal males. 7 Besides this, only little is known about the influence of sex hormones on the male voice in elderly males. Goal of our study was to characterize the association of hormone levels of both kinds of sex hormones-androgens and estrogens-on the elderly male voice-by-voice analysis, videostroboscopy, ultrasonography, and voice-related questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…26 In a study by Gugatschka et al 27 performed on 63 elderly men, voice parameters did not differ in relation to the level of androgen. Androgens did not appear to have an impact on the elderly male voice, whereas estrogen did.…”
Section: Discussionmentioning
confidence: 87%